2020
DOI: 10.3390/genes11030292
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Olfactory Genes in the Expression of Rodent Paternal Care Behavior

Abstract: Olfaction is the dominant sensory modality in rodents, and is crucial for regulating social behaviors, including parental care. Paternal care is rare in rodents, but can have significant consequences for offspring fitness, suggesting a need to understand the factors that regulate its expression. Pup-related odor cues are critical for the onset and maintenance of paternal care. Here, I consider the role of olfaction in the expression of paternal care in rodents. The medial preoptic area shares neural projection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 143 publications
(249 reference statements)
0
16
0
Order By: Relevance
“…Although no studies have specifically examined social discrimination in aging prairie voles, a previous study found that olfactory discrimination abilities are preserved in age and are relatively equivalent in 2-, 10-, and 23-month-old mice [ 66 ]. Indeed, olfactory discrimination abilities are crucial to survival in most rodents [ 67 , 68 ], and it is likely highly adaptable to exhibit preserved sensory function throughout the lifespan of a rodent. Although somewhat different from our findings in the present study, two previous studies using C56BL/6J male mice found that PND180-365 mice engaged in less social contact in a social interaction test with a novel, same-sex juvenile compared to mice aged PND60-150 [ 48 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies have specifically examined social discrimination in aging prairie voles, a previous study found that olfactory discrimination abilities are preserved in age and are relatively equivalent in 2-, 10-, and 23-month-old mice [ 66 ]. Indeed, olfactory discrimination abilities are crucial to survival in most rodents [ 67 , 68 ], and it is likely highly adaptable to exhibit preserved sensory function throughout the lifespan of a rodent. Although somewhat different from our findings in the present study, two previous studies using C56BL/6J male mice found that PND180-365 mice engaged in less social contact in a social interaction test with a novel, same-sex juvenile compared to mice aged PND60-150 [ 48 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…BNST and MeA project to the mPOA, which in turn projects to the lateral preoptic area (LPOA) and substantia innominata (SI). LPOA and SI also send efferents to the ventral tegmental area (VTA), which sends dopaminergic projections to the nucleus accumbens (NAcc) [ 71 , 72 ]. With regard to volatile odor molecules (those that have a low boiling point and evaporate easily at room temperature), they are detected in the roof of the nasal cavity by the main olfactory epithelium (MOE), where olfactory sensory neurons are located.…”
Section: Neural Pathways Underlying Maternal Behaviormentioning
confidence: 99%
“…The sensory capacities of the olfactory system have been particularly well studied in rodents, stimulated by the long tradition of work with laboratory mice and rats (Ferguson, Young, & Insel, 2002;Johnston, 2003), and there is evidence from several rodent taxa that olfaction is used in a variety of social contexts. Odour cues can denote sex, reproductive status (Brennan & Kendrick, 2006) and group membership (Heth, Todrank, & Burda, 2002), mediating a suite of social behaviours involved in mate choice, maternal care, competition and cooperation (Rymer, 2020;Stockley, Bottell, & Hurst, 2013;Willis & Poulin, 2000). For example, in communally nesting house mice, Mus musculus domesticus, females often form nursing partnerships to rear offspring, and prefer nest partners with their own major urinary protein genotype (Green et al, 2015), assessed using unique odour 'signatures' (Roberts et al, 2018).…”
mentioning
confidence: 99%